Transplant renal artery stenosis: The impact of endovascular management and their outcomes - Avinash Bapusaheb Patil (Indian Journal of Urology, 2016)
Introduction: Transplant renal artery stenosis (TRAS) is a well-known vascular complication of renal transplantation. The aim of this analysis was to assess the short and midterm outcomes of endovascular therapy to salvage transplant kidney. Methods: We retrospectively analyzed our transplant database from 2000 to 2015. Percutaneous transluminal angioplasty/stenting was done in 24 patients (22 men and two women) with significant TRAS. The mean age was 59 ± 12 years. The parameters analyzed were: Technical success, pre- and post-treatment serum creatinine and number of antihypertensive drugs before and after treatment and vessel patency on Doppler ultrasonography at 3 and 6 months. Results: Overall incidence of TRAS in this study was 5.06%. Incidence of TRAS following live donor transplantation was 4.68% while that in deceased donors was 11.5%. Technical success was 100%. There were no periprocedural deaths. Renal function was improved from 2.32 ± 0.5 mg/dL to 1.72 ± 0.3 mg/dL (P < 0.001) and number of antihypertensive medications after the procedure was reduced from 2.9 ± 0.7 to 2 ± 0.6 (P < 0.001) at 6 months follow-up. One patient developed restenosis within 5 months (4.2%). Clinical success at 6 months follow-up was 79.2%. Conclusions: Endovascular treatment of TRAS has high technical success with minimal complications. It also provides satisfactory clinical success with improvement in overall transplant renal function and renovascular hypertension in early follow-up.